Management of Diabetic Ketoacidosis: A Summary of the 2013 Joint British Diabetes Societies Guidelines. (July 2014) - Kohler, Katharina; Levy, Nicholas
The purpose of this article is to summarise and to highlight the key points for intensivists from the revised Joint British Diabetes Societies (JBDS) guidelines on the management of diabetic ketoacidosis, which have been endorsed by the Intensive Care Society. Highlights include the following: the use of weight-based fixed-rate intravenous insulin infusion (FRIII); bedside measurement of capillary ketones to monitor response to treatment; use of 0.9% saline with premixed potassium chloride as the main resuscitation fluid on the general medical ward (balanced crystalloids are permitted in intensive care areas where concentrated potassium chloride may be added); hourly measurement of capillary blood glucose; adding 10–20% glucose when the blood glucose falls below 14 mmol/L; continuation of long-acting insulin analogues if the patient is already taking these and referral to intensive care if the patient meets certain criteria. The rationale and the goals of the JBDS guidelines are also described.